A New Species of Heterospio (Polychaeta, Longosomatidae) from Offshore Angola - Bochert, R.; Zettler, M. L. (Zoological Science, 2009)
A new polychaete species of the longosomatid genus Heterospio is described from the coastal shelf off Angola in the Southeast Atlantic. This species was found from two sampling points at depths of 105 and 146 m, and differs from other members of the family in having eight short thoracic setigers, in the lack of neuropodial acicular hooks in the first setiger, and in having only three pairs of branchiae. The material consists of 21 adults with gametes in the body cavity of posterior segments and one juvenile. Size-dependent variation in morphological features such as the length of midbody setigers, number of spines per rami, and occurrence of cinctures, is discussed. A key to the currently recognized species and possible undescribed forms of Heterospio is given.